ANALYSIS OF RAW WATER SUSTAINABILITY AT BABON WATERSHED (A CASE STUDY OF SEMARANG CITY) - M., dkk, Raymond (BPPT)
Babon Watershed (DAS) is one of the watersheds which one located are Central Java. It has been used as a source of raw water for agriculture, industry, drinking water and other household needs. That needs to be assessed the level of sustainability in watershed management of the raw water. This study aims to analyze the sustainability index and the status of management of raw water from the three dimensions of sustainability. Analysis methods used ?multidimensional scaling? (MDS) called Rap WARESMA. The results are expressed in index form and the status of sustainability. The analysis showed that the ecological dimension ofsustainability are at less status (26.54%), dimension less sustainable economicstatus (43.18%) and socio-cultural dimension to the status of sustainable enough(50.83%). Of the 30 attributes that were analyzed contained 15 attributes influencing sensitive to the index and the status of sustainability with a verysmall error at 95% confidence level.keywords: watershed, multidimensional scaling, water, sustainability watershed management